Absolute percentage of biopsied tissue positive for Gleason pattern 4 disease (APP4) appears predictive of disease control after high dose rate brachytherapy and external beam radiotherapy in intermediate risk prostate cancer. (June 2019) - Martell, K.; Mendez, L.C.; Chung, H.; Tseng, C.L.; Zhang, L.; Alayed, Y.; Liu, S.; Vesprini, D.; Chu, W.; Paudel, M.; Cheung, P.; Szumacher, E.; et al.
Highlights: APP4 was predictive of metastatic failure after curative prostate cancer treatment. APP4 was predictive of ADT use for biochemical failure after prostate cancer treatment. APP4 was predictive of biochemical failure after curative prostate cancer treatment. Optimized cutpoints for APP4 were found in this study. Abstract: Background and purpose: To identify if, in intermediate risk prostate cancer (IR-PCa), the absolute percentage of biopsied tissue positive for pattern 4 disease (APP4) may be a predictor of outcome. Materials and methods: 411 patients with IR-PCa were retrospectively reviewed. APP4 was calculated based on biopsy reports. Multivariable competing risk analysis was then performed on optimized APP4 cutpoints to predict for biochemical failure (BF), androgen deprivation use for BF (ADT-BF) and development of metastases (MD). Results: Median follow-up for the cohort was 5.2 (Inter Quartile Range: 2.9–6.6) years. Median baseline PSA was 7.3 (5.3–9.8) ng/mL. 234 (56.9%) patients had T1 and 177 (43.1%) had T2 disease. Median APP4 was 2.00 (0.75–7.50)%. 38 (9.3%) patients experienced BF. The optimal cutpoint of APP4 for BF was >3.3% with an area under the curve (AUC) of 0.66. 17 (4.1%) received ADT-BF. The ADT-BF cutpoint was >6.6% with an AUC of 0.72. Eight (2.0%) developed MD. The MD cutpoint was >17.5% with an AUC of 0.86. Using APP4 >3.3 vs ≤ 3.3, log-transformed baseline PSA ln(PSA) (HR 2.5, 1.1–6.1; p = 0.037) and APP4 (HR 2.3, 1.1–4.7; p = 0.031) predicted for BF. Using APP4 >6.6 vs ≤ 6.6, ln(PSA) (HR 4.2, 1.4–12.4; p = 0.010) and APP4 (HR 3.7, 1.4–10.0; p = 0.009) were predictive of ADT-BF. APP4 >17.5 vs ≤ 17.5 alone was predictive of MD (HR 25.7, 4.9–135.3; p < 0.001). Conclusion: APP4 cutpoints of >3.3%, >6.6% and >17.5% were strongly associated with increased risk of BF, ADT-BF and developing MD respectively. These findings may inform future practice when treating IR-PCa but require external validation.